2020
DOI: 10.21203/rs.3.rs-33577/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal syphilis treatment and pregnancy outcomes: a retrospective study in Jiangxi Province, China

Abstract: Background: Studies investigating the associations of maternal syphilis treatment with birth outcomes mainly concentrated in economically developed areas. Limited data are available in economically underdeveloped areas, such as Jiangxi Province. The study aims to investigate the impact of maternal treatment on birth outcomes in Jiangxi Province, China.Methods: Data were obtained from the China’s Information System of Prevention of Mother-to-Child Transmission in Jiangxi Province. All syphilis infected pregnant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…There was a significant relationship between birth asphyxia and women with syphilis infection. Maternal syphilis infection in pregnancy has been shown in other studies to lead to adverse birth outcomes including; spontaneous abortions, preterm birth, stillbirth and newborns who are small for gestational age [49]. Important to note is that, in Uganda, routine screening for syphilis is done at the initial antenatal visit and treatment offered to those who are infected [28].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant relationship between birth asphyxia and women with syphilis infection. Maternal syphilis infection in pregnancy has been shown in other studies to lead to adverse birth outcomes including; spontaneous abortions, preterm birth, stillbirth and newborns who are small for gestational age [49]. Important to note is that, in Uganda, routine screening for syphilis is done at the initial antenatal visit and treatment offered to those who are infected [28].…”
Section: Discussionmentioning
confidence: 99%
“…The other recommendation for adequate treatment of mother and foetus is that treatment of mother should be completed as early as possible but at least 4 weeks prior to delivery. A study reviewing pregnancy outcomes in women with syphilis in China found significantly higher incidence of adverse pregnancy outcomes in women who were classified as inadequately treated (completed treatment <4 weeks prior to delivery) compared with adequately treated women with an adjusted odds ratio for congenital syphilis of 3.63 (95% confidence interval 1.8-7.31) [49]. Congenital syphilis was not reported in any of the infants from mothers who received treatment in the first trimester, reflecting higher proportion of treatment adequacy when treatment was initiated earlier in pregnancy [49].…”
Section: Management Of the Pregnant Womanmentioning
confidence: 99%
“…Currently, most national studies have only investigated the relationship between treatment during pregnancy and pregnancy outcome in pregnant women with syphilis infection [8][9][10][11], and few studies have evaluated the relationship between their treatment during pregnancy and the conversion of syphilis-specific antibodies in those children exposed to syphilis. It is worth mentioning that the change in serological titers before and after treatment was not identical in each pregnant woman with syphilis infection.…”
Section: Introductionmentioning
confidence: 99%